Study of a phosphorescent cationic iridium(iii) complex displaying a blue-shift in crystals. Issue 43 (29th October 2021) - Martínez-Vollbert, Emiliano; Philouze, Christian; Gautier-Luneau, Isabelle; Moreau, Yohann; Lanoë, Pierre-Henri; Loiseau, Frédérique
Abstract : A joined experimental and theoretical study for unravelling the source of a strong hypsochromism. Abstract : We report the synthesis and the characterization of a new cationic iridium(iii ) complex featuring two 1-( p -methoxyphenyl)-5-methoxybenzimidazole cyclometallating ligands and a dimethylbipyridine ancillary ligand. The complex has been fully characterized by 1D and 2D NMR ( 1 H, 13 C, 19 F and 31 P), elemental analysis and high-resolution mass spectrometry (HRMS). The photoluminescence studies performed in a solution, on amorphous powder and on crystals revealed an unexpected behavior. Indeed, the emission spectra observed in both solution (CH2 Cl2 ) and amorphous powder samples are centered at around 580 nm, whereas in crystals the emission displays a large hypsochromic shift of ∼800 cm −1 ( λ em = 558 nm). X-ray diffraction experiments, photophysical studies and DFT calculations allow for rationalizing the hypsochromic shift.